From welfare state to cessionalism (Economic and Political Thought, 2015)
The author attempts to justify the thesis that Schumpeter’s theory onthe phenomena leading to its destruction works in the current version ofneoliberal capitalism. What Schumpeter was most concerned about, namely theconsequences of the deformation of the principles of freedom and the systemof private ownership let corporations grow extremely fast and made it possibleto eliminate ordinary entrepreneurs and their innovation. The process is takingon such alarming proportion that former Schumpeter’s predictions of whatwould happen in the future as a result of the growth of corporate capitalism arealready reflected in reality. In the author’s opinion, the neoliberal doctrine isbased on false premises among which Milton Friedman’s claim that stagflationis always and everywhere a Keynesian phenomenon is of key importance.Therefore, there is a need for creative destruction in the doctrinal sphereaimed against neoliberalism and making it possible to introduce innovativesolutions that were wrongly eliminated. But it will not be enough to reintroducethe rules of welfare state. Great success of the United States in the period oftheir implementation originated from, besides the innovation in the politicalsystem, other sources of extraordinary prosperity. These were huge profitsfrom seigniorage at the stage of the dollar progression. At present, it wouldbe desirable that the United States should restore full trust in the dollar asa dominant world currency. Based on the arguments presented in the article,there is a call for saving capitalism from a collapse with the use of a solutionconsisting in the development of a new version of capitalism called cessionalism.